IDENTIFIKASI JENIS POHON DI HUTAN PENDIDIKAN UNIVERSITAS SUMATERA UTARA - Anna O Simalango; Agus Purwoko; Siti Latifah (Peronema Forestry Science Journal, 2015)
This study was conducted to identifify trees in university of north sumatera education forest, Tongkoh, Karo District, North Sumatera Province. This study was conducted in June 2014. The collecting of data used path method, and the sampling technique used purposive sampling with random start method. Plot size 100m x 20m of 10 plots categorized as large plot to observe trees with diameter > 30 cm at the and there was subplots with size 5m x 40m categorized as small plot to observe trees with diameter 5m to 30cm. The results showed that 46 species of trees are derived from 29 families.Keywords:  Trees species , education forest University of  North Sumatera